Enantioselective acyl transfer catalysis by a combination of common catalytic motifs and electrostatic interactions - Mandai, Hiroki (Nat Commun, 2016)
Catalysts that can promote acyl transfer processes are important to enantioselective synthesis and their development has received significant attention in recent years. Despite noteworthy advances, discovery of small-molecule catalysts that are robust, efficient, recyclable and promote reactions with high enantioselectivity can be easily and cost-effectively prepared in significant quantities (that is, >10 g) has remained elusive. Here, we demonstrate that by attaching a binaphthyl moiety, appropriately modified to establish H-bonding interactions within the key intermediates in the catalytic cycle, and a 4-aminopyridyl unit, exceptionally efficient organic molecules can be prepared that facilitate enantioselective acyl transfer reactions. As little as 0.5 mol% of a member of the new catalyst class is sufficient to generate acyl-substituted all-carbon quaternary stereogenic centres in quantitative yield and in up to 98:2 enantiomeric ratio (er) in 5 h. Kinetic resolution or desymmetrization of 1,2-diol can be performed with high efficiency and enantioselectivity as well.